The effect of oral immunotherapy treatment in severe IgE mediated milk, peanut, and egg allergy in adults - Mäntylä, Jarkko (Immun Inflamm Dis, 2018)
INTRODUCTION: The standard care of severe food allergy in both adults and children means avoidance of allergens. In recent years promising results of oral immunotherapy (OIT) have been reported in children. In adults, information on OIT in severe food allergy is very limited. OBJECTIVE: We aimed to study if OIT is possible in adults. METHODS: We report OIT results in 10 adult patients with milk OIT, nine adult patients with peanut OIT, and four adult patients with egg OIT. The allergy was confirmed with allergen specific IgE tests and oral food challenges (open in milk allergy and double‐blind in peanut and egg allergy). The OIT was performed as open. RESULTS: The median dose of protein that led to discontinuation of allergen challenge because of symptoms was 7.5 mg in milk allergy, 25 mg in peanut allergy, and 15 mg in egg allergy. The median period of OIT was 515 days. Currently on OIT are 6/10 milk allergic patients, 4/9 peanut allergic patients and 3/4 egg allergic patients. The median dose of milk protein increased by 60‐fold during OIT compared to the allergen challenge dose. In peanut OIT the median dose increased by eightfold and in egg allergy the dose increased with OIT by 35‐fold. Local itching was the most common side effect of OIT (73.9% of the patients), four patients reported having used epinephrine autoinjector and three patients having needed emergency room treatment. CONCLUSIONS AND CLINICAL RELEVANCE: OIT can be given in adult patients with severe milk, peanut, or egg allergy only in selected cases. OIT leads into desensitization but it is not clear whether persistent tolerance can be achieved. Mild adverse events during OIT are common.